Pemberdayaan Desa Luwuk Rangan Kecamatan Cempaga Kabupaten Kota Waringin Timur sebagai Sentral Produksi Kerajinan Tangan Khas Kalimantan Berbasis Digital: Empowering Luwuk Rangan Village, Cempaga District, East Waringin Regency, as a Digital-Based Center for Kalimantan Handicraft Production - Suriansyah, Suriansyah; Haryadi, Haryadi; Haq, Muhammad Achiril; Suwandini, Najwa Aulia; Wahyuni, Laras Intan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Kalimantan's distinctive rattan crafts have high cultural value, but their development is still hampered by limited digital marketing. The community service program in Luwuk Rangan Village, Cempaga District, East Kotawaringin Regency aims to enhance the digital skills of the Handep Lewu artisan group, enabling them to expand their market reach and increase the competitiveness of their products. The implementation methods include planning, digital literacy socialization, training in promotional content creation, craft-making practice, and the application of e-commerce technology. The results of the activities show an increase in the artisans' ability to utilize social media, produce digital content, and use e-commerce platforms as a means of transaction. Thus, this program has succeeded in strengthening the artisans' capacity to adapt to technological developments while supporting the sustainability of the creative economy based on local culture.